2013
DOI: 10.1021/es401356v
|View full text |Cite
|
Sign up to set email alerts
|

Global Civil Aviation Black Carbon Emissions

Abstract: Aircraft black carbon (BC) emissions contribute to climate forcing, but few estimates of BC emitted by aircraft at cruise exist. For the majority of aircraft engines the only BC-related measurement available is smoke number (SN)-a filter based optical method designed to measure near-ground plume visibility, not mass. While the first order approximation (FOA3) technique has been developed to estimate BC mass emissions normalized by fuel burn [EI(BC)] from SN, it is shown that it underestimates EI(BC) by >90% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 34 publications
(83 reference statements)
4
79
2
Order By: Relevance
“…However, the previous soot emission measurements were taken behind aircraft with low power settings. Recent studies suggest a significant increase in the emission index of black carbon mass for higher fuel flows (Stettler et al, 2013). New evidence based on our observations shows that the soot emissions may have been underestimated and at least as high as 1.0 × 10 15 kg −1 (Schumann et al, 2013), leading to further uncertainties in the initial ice crystal number.…”
Section: Atmospheric Conditions and Contrail Initializationmentioning
confidence: 61%
“…However, the previous soot emission measurements were taken behind aircraft with low power settings. Recent studies suggest a significant increase in the emission index of black carbon mass for higher fuel flows (Stettler et al, 2013). New evidence based on our observations shows that the soot emissions may have been underestimated and at least as high as 1.0 × 10 15 kg −1 (Schumann et al, 2013), leading to further uncertainties in the initial ice crystal number.…”
Section: Atmospheric Conditions and Contrail Initializationmentioning
confidence: 61%
“…Lack et al, 2009). Aviation contributes only a very small proportion of global PM emissions; for example, for black carbon its share was estimated at about 0.1-0.2 % Stettler et al, 2013), of which about 14 % was during landing and take-off (LTO) (Stettler et al, 2013). …”
Section: International Shipping and Aviationmentioning
confidence: 99%
“…The measurement of EI(BC) by several studies (Herndon et al, 2008;Onasch et al, 2009;Timko et al, 2010) indicates that EI(BC) spans around 4 orders of magnitude. Stettler et al (2013) discuss and quantify the underestimation of EI(BC) observed in currently available aircraft BC emissions inventories. In this regard, a previous study (Stettler et al, 2011) has stated: "The First-Order Approximation (FOA3) -currently the standard approach used to estimate particulate matter emissions from aircraft -is compared to measurements and it is shown that there are discrepancies greater than an order of magnitude for 40 % of cases for both organic carbon and black carbon emissions indices".…”
Section: Prescription Of Aircraft Bc Emissionsmentioning
confidence: 99%
“…In this regard, a previous study (Stettler et al, 2011) has stated: "The First-Order Approximation (FOA3) -currently the standard approach used to estimate particulate matter emissions from aircraft -is compared to measurements and it is shown that there are discrepancies greater than an order of magnitude for 40 % of cases for both organic carbon and black carbon emissions indices". Thus, to assess this inventory over Hyderabad (our study region), we estimated BC emissions from aircraft over this region using previously reported values for the fuel efficiency of different airline carriers (Kwan and Rutherford, 2015), seating capacity of the carriers (websites of different airlines), density of aviation fuel used (Cookson and Smith, 1990;Arkoudeas et al, 2003;Outcalt et al, 2009;Blakey et al, 2011) in the Indian region, BC emission index for the aviation fuel (Stettler et al, 2013) and actual data on air traffic over Hyderabad obtained from air traffic control (Babu et al, 2011). Depending on such an evaluation of the MACCity emissions database over the Hyderabad region, we have modified the inventory emissions by a corresponding scaling factor.…”
Section: Prescription Of Aircraft Bc Emissionsmentioning
confidence: 99%